Comparison of Challenges Facing Indonesian Peasants with Uganda Coffee Peasants - Musilike, Badru; Saragih, Mujahid Widian (Jurnal Kajian Agraria dan Kedaulatan Pangan (JKAKP), 2024)
This study explains the comparison of challenges between Indonesian peasants (Mandoge) and Ugandan coffee peasants using a critical, systematic, and comparative qualitative research approach. Several sources used are the researcher's direct experience, books, journals, and other scientific works. The results of the study show that the challenges of Mandoge peasants and coffee peasants in Uganda have many similarities and also have differences that are not so significant. Both Mandoge peasants and Ugandan coffee peasants have the same challenges, namely experiencing land grabbing and eviction by companies and are certainly related to the government. Furthermore, to overcome this, they both established cooperatives which ultimately also went bankrupt. Meanwhile, in terms of differences, Mandoge peasants are more aware and willing to find solutions to the incidents that befell them, while Ugandan coffee peasants seem to be stagnant or confused about how to act due to lack of knowledge. However, in reality, land evictions in any world are not commendable actions that can be carried out arbitrarily because they are in power.